Efeitos renais dos hipoglicemiantes orais derivados das sulfonamidas, incretinas e inibidores de SGLT2, no escape renovascular e na estimulação alfa adrenérgica, em coelhos - Farias, Jéssica Alves (2020)
The use of renal perfusion techniques has been shown to be advantageous, as it allows advances in the understanding of the tubular mechanisms of ion resorption in the renal system of several animal species. Because of this, the renal vascular system is the target of countless scientific studies about the vasoactive and reactive characteristics of substances that modulate some pathophysiology. In this sense, California rabbits, from the Cuniculture Department of Zootechnics of the Federal University of Ceará, were used in order to assess the renovascular effects and alpha adrenergic stimulation in normoglycemic animals, produced by oral hypoglycemic agents used clinically to control changes glucose levels of diabetes mellitus. The project was initiated after approval by the Ethics Committee on the Use of Animals of the Federal University of Ceará (CEUA-UFC) under number 9768280219 and the experiments were conducted according to the Brazilian legislation that regulates the use of animis in scientific experiments, as the Arouca Law 11974 of 2008. All oral antidiabetic substances used were prepared, diluted and added to the KH solution, for subsequent renal infusion, through the perfusion system. Several physiological parameters were evaluated in order to evaluate the effects of these oral antidiabetics in normal rabbits, in the perfused kidney, during α-adrenergic vascular interaction. Regarding the perfusion pressure, all groups showed a peak pressure higher than the control group with the addition of PHE, proving the interference of oral antidiabetics in the pressure levels of the renal perfusion system. However, only the group with the addition of empaglifozin was able to demonstrate the presence of the tachyphilatic effect, similar to that presented by the control group, exhibiting a drop in maximum blood pressure values throughout the entire experiment. All groups of oral hypoglycemic agents demonstrated vascular resistance greater than that of the control group with the addition of PHE, with the greatest resistance being the empaglifozin and glimepiride groups, this result being linked to the values of perfusion pressure and perfusate flow, due to the formula used to perform the calculation of this measure . On the other hand, the group with addition of gluclaside was the only group capable of overcoming the results presented by the control group with PHE infusion, in relation to the RFG. In addition to the glomerular filtration rate, gluclaside also demonstrated significant relevance in relation to osmolar clearance and free water clearance.